Strategi Pengembangan Bisnis Startup Menggunakan SWOT Analysis (Studi Kasus pada Startup yang Terdaftar di Bursa Efek Indonesia) - Ni Made Dian Kemala Ratih Palgunadi (Departement of Mathematics Education, 2023)
Startups in Indonesia that are growed fast and have an impact on the national economy. The high enthusiasm of the people is proven by Indonesia being included in the five countries with the highest number of startups in the world. There are several startups with good financial valuations that can be classified as unicorns or even decacorns. In the capital raising process, of course, it cannot be separated from the strategies taken by the company; one of the funding alternatives is to conduct an initial public offering (IPO) on the Indonesia Stock Exchange (IDX). Until 2022, the only startups that have conducted an IPO are PT. Bukalapak.com (BUKA) and PT. Goto Gojek Tokopedia (GOTO). analyzing the two companies' business strategy models using a strength, weakness, opportunity, and threat (SWOT) analysis.The method used in this study is a descriptive qualitative method, and the process of collecting data is by conducting literature studies from sources of scientific publications and accredited digital news.